Correlation Between Epidural Hematoma Volume in Temporal Region with Glasgow Coma Scale on Patients with Head Injury at Haji Adam Malik General Hospital Medan in the year of 2018 - Pandiangan, Ruth Jean Tri Apriliyanty (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Epidural hematoma (EDH) is the type of intracranial haemorrhage due to head injury that occur most frequently. EDH volume usually stable and can reach the maximum volume in only a few minutes or hours after traumatized. EDH being attentive to the clinicians and researchers because of the enforcement diagnosis that is relatively easy and the rate of success in operation is quite high and EDH located in temporal region contributed to increasing the mortality due to respiratory arrest from uncal herniation because of brainstem compression. Measuring degrees severity EDH the most common and much worn in international is glasgow coma scale (GCS) because it has a high level of validity; reliability, sensitivity and specificity. This research was conducted to see correlation between EDH volume in temporal region with GCS in patients with head injury. Research conducted is analytic observation with cross-sectional approached study. The study sample is 45 epidural hematoma patients in temporal region at productive age (18-59 years) who had diagnosed and got the best act of resuscitating to know the score GCS at H. Adam Malik General Hospital in 2018 who had met the inclusion and exclusion criteria. The technique of taking data is consecutive sampling from medical record. Statistically there are negative relations between GCS to the volume of EDH patients based on the results of the CT scan (p<0,001, CI 95 %) with the 0,619 relations that is indicative of the strength of the relations which is very strong.